2015
DOI: 10.1177/0004867415569802
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review: Identifying the prevalence rates of psychiatric disorder in Australia’s Indigenous populations

Abstract: It was identified that there is limited evidence on the occurrence of psychiatric disorders for Indigenous people in the general community. More research in this area is essential to provide accurate and reliable estimates and to provide a baseline for evaluating the effectiveness of programs aimed at reducing the high mental health burden experienced by Indigenous Australians. Future research needs to ensure that standardised and validated methods are used to accurately estimate the prevalence of psychiatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
59
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 32 publications
1
59
0
3
Order By: Relevance
“…Whilst the physical health of these groups is well-understood, mental health is not as well-researched however. Previous reviews have attempted to identify rates of psychiatric disorders in Indigenous Australians (Black et al, 2015) and New Zealanders (Baxter, 2008), with varying findings. For instance, Black et al found wide variability in the rates of psychiatric disorder for Indigenous Australians, with some studies reporting high rates (up to approximately 50% of participants) for anxiety and mood disorders.…”
Section: Australia and New Zealand's (Nz) Indigenous Populations Commentioning
confidence: 99%
“…Whilst the physical health of these groups is well-understood, mental health is not as well-researched however. Previous reviews have attempted to identify rates of psychiatric disorders in Indigenous Australians (Black et al, 2015) and New Zealanders (Baxter, 2008), with varying findings. For instance, Black et al found wide variability in the rates of psychiatric disorder for Indigenous Australians, with some studies reporting high rates (up to approximately 50% of participants) for anxiety and mood disorders.…”
Section: Australia and New Zealand's (Nz) Indigenous Populations Commentioning
confidence: 99%
“…), and higher levels of psycopathology (Black et al . ). This has led to Indigenous leaders and researchers alike examining a range of solutions to the many complex issues involved (Ridani et al .…”
mentioning
confidence: 97%
“…Por lo anterior, entre los adultos mayores indígenas son frecuentes las enfermedades crónicas y son estas la causa principal de mortalidad. Asimismo, la prevalencia de trastornos mentales en estos contextos suele ser mayor en comparación con otros grupos poblacionales (5). Sin embargo, la incidencia de demencia y deterioro cognitivo leve todavía no se ha definido.…”
unclassified